Living on the fringes of a protected area: Gonarezhou National Park (GNP) and the indigenous communities of South East Zimbabwe 1934-2008 - Mlambo, Alois S. (University of Pretoria, 2016)
Thesis (DPhil)--University of Pretoria, 2016.